MENINGKATKAN KETERAMPILAN MOTORIK HALUS ANAK MELALUI KEGIATAN MEWARNAI GAMBAR DENGAN PASIR BERWARNA PADA ANAK USIA (5-6) TAHUN DI TK TABITHA 1 KELURAHAN BENTENG KOTA AMBON - Gracia Sitaniapessy; Rosmaryn Tutupary; Junita. L. Kundre (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study addresses the low development of fine motor skills among 5–6-year-old children at TK Tabitha 1 Benteng, Ambon City, characterized by poor hand–eye coordination, difficulty grasping pencils, and limited dexterity during coloring activities due to insufficient stimulation and monotonous learning methods. The research aimed to improve children's fine motor skills through coloring activities using colored sand. Employing a classroom action research design based on Kurt Lewin's model, the study was conducted over two cycles comprising four meetings with 13 children as subjects. Data were collected through observation sheets and documentation, then analyzed descriptively. Results showed significant improvement: in the pre-cycle, 61.53% of children were categorized as